A Letter of Consequence: Referral Letters from General Practitioners to Secondary Mental Health Services - Shaw, Ian; Clegg Smith, Katherine M; Middleton, Hugh; Woodward, Louise
The referral letter is a key instrument in moving patients from primary to secondary care services. Consequently, the circumstances in which a referral should be made and its contents have been the subject of clinical guidelines. This article is based on a project that demonstrated that physicians do not adhere to clinical guidelines when referring patients to secondary mental health services. This research supports earlier findings into noncompliance with guidelines by general practitioners (GPs). The authors briefly note possible reasons, which have been the subject of some debate. They also present a content analysis of referral letters to demonstrate the important ways in which they differ from guideline criteria. However, their central argument is that the role of the referral letter in relation to the GP’s repertoire of treatments has not been understood fully. Such understanding implies the need for a reexamination of the support available for GPs.